Rapid NMR-scale purification of 15N,13C isotope-labeled recombinant human STIM1 coiled coil fragments - Rathner, Petr; Stadlbauer, Michael; Romanin, Christoph; Fahrner, Marc; Derler, Isabella; Müller, Norbert (Protein expression and purification, 2018)
We report a new NMR-scale purification procedure for two recombinant wild type fragments of the stromal interaction molecule 1 (STIM1). This protein acts as a calcium sensor in the endoplasmic reticulum (ER) and extends into the cytosol accumulating at ER - plasma membrane (PM) junctions upon calcium store depletion ultimately leading to activation of the Orai/CRAC channel. The functionally relevant cytosolic part of STIM1 consists of three coiled coil domains, which are mainly involved in intra- and inter-molecular homomeric interactions as well as coupling to and gating of CRAC channels. The optimized one-step rapid purification procedure for two 15N,13C isotope-labeled cytosolic coiled coil fragments, which avoids the problems of previous approaches. The high yields of soluble well folded 15N,13C isotope-labeled cytosolic coiled coil fragments followed by detergent screening provide for initial NMR characterization of these domains. The longer 30.5 kDa fragment represents the largest STIM1 wild type fragment that has been recombinantly prepared and characterized in solution without need for mutation or refolding.
Keywords: Electrophoresis, Polyacrylamide Gel; izotopy uhlíku; Nitrogen Isotopes; dynamický rozptyl světla; proteinové domény; lidé; Carbon Isotopes; rekombinantní proteiny; Recombinant Proteins; Isotope Labeling; Solubility; rozpustnost; Protein Domains; protein STIM1; Nuclear Magnetic Resonance, Biomolecular; izotopové značení; sbalování proteinů; Protein Folding; nukleární magnetická rezonance biomolekulární; izotopy dusíku; Chromatography, Affinity; nádorové proteiny; Neoplasm Proteins; Stromal Interaction Molecule 1; elektroforéza v polyakrylamidovém gelu; Dynamic Light Scattering; chromatografie afinitní; Humans